Classes of operators related to binormal operators - Kikete Wabuya; Stephen Luketero Wanyonyi; Justus Kitheka Mile; Arthur Wafula W. Wanyonyi (Scientific African, 2023)
Binormal operators play a key part in the study of operator theory, particularly in testing spectral algorithms. A new class of operators known as the (n,m)-binormal operators is introduced in this paper, then we study its characteristics and relationship with other classes of operators. It is shown that if an operator T is (n,m)-binormal, and is unitarily quasiequivalent to an operator S, then S is also (n,m)-binormal.